STRUCTURAL CONSTRUCTION OF THE HARDENERS WITH DIFFERENT HARDENING RATES INTENDED FOR GEOPOLIMER BINDER SYSTEMS USED FOR THE PREPARATION OF MOULDING SANDS (Metallurgy and Foundry Engineering, 2016)
The paper presents the results of structural investigations of hardeners series of different hardening rate of the geopolymer Geopol, manufactured by the Sand-Team Company. Studies showed that these hardeners have the similar chemical structure and that the hardening rate of the binder depends on the proper selection of the proportions of respective components.